2017
DOI: 10.12659/aot.905347
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Perfusate from Machine Cold Perfusion of Transplant Kidneys: Insights Into Protection from Injury

Abstract: BackgroundMachine cold perfusion is beneficial to the preservation of kidneys for transplantation. At the end of preservation, the perfusion solution contains many proteins. Using a proteomics approach, we searched for useful biomarkers and potential therapeutic targets in the perfusate. Our program is unique in that all transplant kidneys (even living donor kidneys, LKD) are placed on machine cold perfusion prior to transplantation.Material/MethodsPerfusates from donation after neurological and circulatory de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…LDH, neutrophil gelatinase-associated lipocalin (NGAL), and matrix metalloproteinase-2 levels were highest in DCD kidneys, followed by DBD and living-donor (LD) kidneys. Other molecules, such as periredoxin-2 and α-1 antitripsin, were also significantly different across the three groups, probably reflecting different degrees of IRI [ 14 , 15 ]. Exosomal mRNA for NGAL and NGAL concentration in the perfusate of machine-perfused kidneys were associated with DGF also in another study [ 15 ].…”
Section: Iri and Dgfmentioning
confidence: 99%
“…LDH, neutrophil gelatinase-associated lipocalin (NGAL), and matrix metalloproteinase-2 levels were highest in DCD kidneys, followed by DBD and living-donor (LD) kidneys. Other molecules, such as periredoxin-2 and α-1 antitripsin, were also significantly different across the three groups, probably reflecting different degrees of IRI [ 14 , 15 ]. Exosomal mRNA for NGAL and NGAL concentration in the perfusate of machine-perfused kidneys were associated with DGF also in another study [ 15 ].…”
Section: Iri and Dgfmentioning
confidence: 99%
“…In a prior study, we documented the differences in proteins released into the perfusate during machine cold perfusion [34]. This revealed very different proteins alpha-1-antitrypsin, peroxiredoxin-2, and neutrophil gelatinase-associated lipocalin (NGAL -a standard marker of renal injury) being released during preservation injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the level of Prx2 in perfusion solution can be an important prognostic factor in cold perfusion of isolated kidneys. The kidney perfusate from living donors had a significantly higher level of Prx2, compared to that from dead donors, allowing the donor kidney to be more “prepared” for reperfusion-mediated oxidative stress and increasing the chances for success of its transplantation [ 92 ].…”
Section: Discussionmentioning
confidence: 99%